A Pilot Study to Assess Patient Adherence to New Chronic Medications Following the Use of a Novel Adherence Tool and Individualized Counseling. (December 2015) - Treadway, Sarah A.; Helmer, Robert S.; Farland, Michelle Z.; Ray, Shaunta M.
Background: Medication nonadherence leads to an increase in morbidity and mortality. In the United States, it results in an annual estimated cost of 290 billion in patients with chronic diseases. Several adherence screening tools are available for use, but none have been adopted for widespread use.Objective: Examine the impact of using a novel 3-item adherence tool (The Adherence Estimator) and individualized patient counseling on medication adherence, as determined by rate of initial prescription fill.Methods: This prospective, descriptive study enrolled patients discharged home from an inpatient adult family medicine service who received a prescription for at least one new chronic medication. Patients completed the Adherence Estimator survey for each new medication prescribed. All patients received counseling from a pharmacist or student pharmacist. Date of initial fill was determined by contacting the dispensing pharmacy.Results: The survey was completed for 79 medications. The rate of first fill for medications identified as low, medium, and high risk for nonadherence was 76.5% (n = 28), 71.4% (n = 20), and 94% (n = 17), respectively.Conclusions: The brevity of The Adherence Estimator and the ease of scoring allow the possibility of adoption for widespread clinical use. The survey permits immediate results that allow the clinician to tailor medication counseling toward the 3 most common predictors of nonadherence. The rate of first fill for medications classified as high risk was improved following administration of the tool and targeted medication counseling, 94% in our population compared to predicted probability of adherence of <32%. Several factors, including targeted counseling or study/tool limitations, could account for these results. Consideration should be given to revising the statements in the tool to a lower reading level. This screening tool provides significant advantages over available tools; however, further research is needed to determine the most appropriate population and setting for use of this tool.